2018
DOI: 10.1021/jacs.7b13077
|View full text |Cite
|
Sign up to set email alerts
|

Development of a UiO-Type Thin Film Electrocatalysis Platform with Redox-Active Linkers

Abstract: Metal-organic frameworks (MOFs) as electrocatalysis scaffolds are appealing due to the large concentration of catalytic units that can be assembled in three dimensions. To harness the full potential of these materials, charge transport to the redox catalysts within the MOF has to be ensured. Herein, we report the first electroactive MOF with the UiO/PIZOF topology (Zr(dcphOH-NDI)), i.e., one of the most widely used MOFs for catalyst incorporation, by using redox-active naphthalene diimide-based linkers (dcphOH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
138
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(142 citation statements)
references
References 92 publications
3
138
0
1
Order By: Relevance
“…As revealed in Figure c and Figure d, both plots show great linearity, which suggests that the electrochemical reaction of Mn(III)/Mn(IV) occurring in the Mn‐UiO‐66 thin film is diffusion‐controlled; the diffusion behavior here represents the charge hopping between adjacent manganese sites and the diffusion of counterions within the framework. [14a], [15c], [20b] Amperometric experiments were then performed with the Mn‐UiO‐66 thin film (Figure e), and the apparent diffusivity ( D app ) can be calculated from Figure f by utilizing the Cottrell equation [Equation (1)]. [20b] J= nF D app 0.5 C π 0.5 t 0.5 where J is the current density, n is the number of electron involved in the reaction, which is 1 for Mn(III)/Mn(IV), F is Faraday constant, t is time, and C is the concentration of redox‐active Mn sites presented within the MOF thin film.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As revealed in Figure c and Figure d, both plots show great linearity, which suggests that the electrochemical reaction of Mn(III)/Mn(IV) occurring in the Mn‐UiO‐66 thin film is diffusion‐controlled; the diffusion behavior here represents the charge hopping between adjacent manganese sites and the diffusion of counterions within the framework. [14a], [15c], [20b] Amperometric experiments were then performed with the Mn‐UiO‐66 thin film (Figure e), and the apparent diffusivity ( D app ) can be calculated from Figure f by utilizing the Cottrell equation [Equation (1)]. [20b] J= nF D app 0.5 C π 0.5 t 0.5 where J is the current density, n is the number of electron involved in the reaction, which is 1 for Mn(III)/Mn(IV), F is Faraday constant, t is time, and C is the concentration of redox‐active Mn sites presented within the MOF thin film.…”
Section: Resultsmentioning
confidence: 99%
“…To facilitate charge transport within the Zr‐MOFs for electrochemical applications, a more common strategy is to utilize the redox hopping pathway . As the zirconium‐based nodes in Zr‐MOFs are redox‐innocent, the charge transport via redox hopping in Zr‐MOFs must be supported by the redox‐active linkers or species installed on the nodes . With the help of the redox hopping pathway, various Zr‐MOFs have been found to be electrochemically addressable and utilized in a range of electrochemical applications, including electrochromic glass, oxygen evolution,[15c], oxygen reduction, carbon dioxide reduction and electrochemical sensors .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2022 In this context, several groups have developed MOFs that show PCET behavior resulting in good photo- and electro-chemical activities. 2224 PCET has been suggested to occur on the linker, 24 the node, 25 and the linker and node combined 22,23 but has not been studied in well-known photoactive MOFs. In this work, we provide an in-depth analysis of the PCET behavior in the widely used MIL-125.…”
Section: ■Introductionmentioning
confidence: 99%
“…Spectroelectrochemical analysis revealed that charge transport occurred via linker‐to‐linker hopping, balanced by ion transport from the electrolyte. Changing the electrolyte cation from n ‐Bu 4 NPF 6 to KPF 6 increased the effective diffusion coefficient from 4.0 × 10 −12 cm 2 s −1 to 5.4 × 10 −11 cm 2 s −1 , highlighting the effects of ion diffusion through the film on the resultant conductivity (Johnson et al ). While these diffusion coefficients are quite low, the use of MOF and COF thin films on the order of ∼1 μm alleviates these conductivity limitations.…”
Section: Mof and Cof Interfaces And Electrochemistrymentioning
confidence: 99%